THE THIN LINE BETWEEN FUNNY AND DISRESPECTFUL: MEDIA FRAMING ON PRABOWO’S ”BOYOLALI FACE” REMARK - Fikry Zahria Emeraldien; Rahma Sugihartati; Kinanti Resmi Hayati (Universitas Pendidikan Ganesha, 2021)
The 2019 Indonesian Presidential Election is a democratic process for electing the President and Vice President of the Republic of Indonesia for the 2019-2024 period. Before the election was held, Indonesia's mass media was incessantly publishing news about presidential candidates, namely Joko Widodo and Prabowo Subianto Djojohadikusumo. As a retired army lieutenant general, Prabowo is known as a nationalist figure. This research aims to study Prabowo's image just before the 2019 Election in the online version of print media. We examine and compare the construction of Prabowo's image carried out by Tempo.co and Republika.co.id. We purposively select news published in Tempo and Republika online version from 4 to 5 November 2019. This research uses the qualitatively framing method by Entman to answer how the mass media carry out image construction. Results indicate that both media carry out a difference between construction. If Tempo tends to construct Prabowo's image as disrespectful, Republika tends to construct Prabowo's image as funny regarding Prabowo's